Tinjauan Atas Penjualan dan Pendapatan Sales PT Rohto Laboratories Indonesia Pada Supermarket Yogya Cimanggu - Uning Widiastuti; Aang Munawar (Jurnal Aplikasi Bisnis Kesatuan, 2022)
Sales is the activity or business of selling products or services. In the process of selling, the seller or provider of goods and services gives ownership of a commodity to the buyer for a certain price. Revenue is the ability of a company to finance all costs and operations are strongly influenced by its income. The higher the income received, the greater the company's ability to finance all its expenses and activities. Revenue is obtained from various sources, one of which is sales. Sales made include sales procedures within the company. The purpose of this study was to determine the sales procedures of PT Rohto Laboratories Indonesia at Yogya Cimanggu, to see the suitability of the sales procedures carried out and to know the revenue receipt system. The results of the evaluation in the review that the authors carried out showed that the sales procedures of PT Rohto Laboratories Indonesia at Yogya Cimanggu and the revenue receipt system for Yogya Cimanggu's sales at PT Rohto Laboratories Indonesia had run well in accordance with the applicable procedures. Keywords : Sales Procedures, Revenue